Salt stress and UV-B radiation modulate growth, physiology and 20-hydroxyecdysone contents in Brazilian-ginseng [Pfaffia glomerata (Spreng.) Pedersen] - Felipe, Sérgio Heitor Sousa (2019)
The phytoecdysteroid 20-hydroxyecdysone (20E) is a secondary metabolite with high agrochemical, biotechnological and pharmacological potential, produced only by certain plant species. However, in relation to 20E, it is emphasized that: (i) the biosynthetic pathway is not fully elucidated in plants; (ii) it is not clear its real function in plants; (iii) there are few morphophysiological and molecular studies in plants that produce this metabolite; and (iv) there is a need to investigate the induction, biosynthesis, regulation and translocation of this metabolite in plants. In this sense, two experiments were performed aiming to evaluate the impact of salt stress and UV-B radiation on growth, physiology, expression of key genes involved in the biosynthesis and the 20E content in Pfaffia glomerata. In the first experiment, accession 43 (A43) plants with 40-day-old grown in greenhouse were exposed to 0-, 120-, 240-, 360- and 480-mM sodium chloride (NaCl) for 11 consecutive days. In the second experiment, two accessions (A22 and A43) plants with 20-day-old grown in in vitro were exposed to 0-, 2- and 4-h UV-B radiation for 20 consecutive days. Mild salt stress (i.e., 120 mM NaCl) increased 20E concentrations in the leaves (47%) relative to the control, with no significant effect on photosynthesis and biomass accumulation. In contrast, plants under severe salt stress (i.e., 240 to 480 mM NaCl) did not increase 20E concentrations compared to the control. Additionally, severe salt stress caused marked damage in biomass accumulation and photosynthetic performance in parallel with the nutritional imbalance. To combat severe salt stress, P. glomerata plants displayed an increase in salicylic acid levels, antioxidant enzyme activities and osmoregulatory status (e.g., glucose, fructose, total amino acids, and proline). UV-B radiation differentially impacted the accessions A22 and A43. In A22, 4 h of exposure reduced biomass accumulation and electron transport rate, on the other hand, increased antioxidant activity (e.g., peroxidases), while A43 did not vary for these characteristics. Besides, only A22 increased the 20E concentration under 2 and 4 h of UV-B in leaves (28 and 21%, respectively) and roots (16 and 13%, respectively). This contrasting performance between A22 and A43 to UV-B radiation can be explained by A43 displayed 56% more anthocyanin to the former, a possible defense against UV-B. In both experiments, the production of 20E was accompanied by an upregulation of Spook and Phantom genes. The results of this work bring an unprecedented better understanding of the 20E regulation under conditions of abiotic stresses (salt stress and UV-B radiation). Finally, we provide findings that can be applied to increase 20E levels and contribute to the development of biotechnology, pharmacology and ex vitro and in vitro culture of the species.